A 75-year old woman with undiagnosed Behcet's disease presenting with recurrent thromboembolism and aortic disection:A multidisciplinary Perspective - Arbutina, Suzana; Dimitrovska, Irena; Pejkovska, Sava (Association of Traditional Chinese Medicine and Acupuncture Tong da Tang, 2024)
Behçet's disease (BD) is a systemic vasculitis characterized by recurrent oral and genital ulcers, uveitis, and skin lesions, often leading to severe vascular complications, including recurrent thromboembolism and aortic dissection. While its etiology remains uncertain, BD is thought to involve genetic predisposition and environmental triggers, with associations to HLA-B51 particularly prevalent among populations along the historical Silk Road. Diagnosing BD is challenging due to its diverse symptoms and lack of specific biomarkers, necessitating a holistic approach that considers a wide array of clinical, serological, and imaging findings. This report presents the case of a 47-year-old woman with previously undiagnosed BD who developed severe complications, including aortic dissection and pulmonary embolism. A multidisciplinary approach was critical in recognizing the systemic nature of her condition, eventually confirming BD through the combination of vascular involvement, mucocutaneous symptoms, and a positive HLA-B51 marker. Following diagnosis, targeted treatment involving immunosuppressive therapy and anticoagulation led to significant improvement. This case underscores the importance of a comprehensive, interdisciplinary perspective in managing BD, especially in complex cases where symptoms span multiple organ systems. Further research into BD’s underlying mechanisms and more effective, integrative treatment approaches is essential to improve patient outcomes.
Keywords: Behçet’s Disease; Thromboembolism; Management and Treatment